Genotype Diversity of Mycobacterium bovis and Pathology of Bovine Tuberculosis in Selected Emerging Dairy Regions of Ethiopia - Mekonnen, Getnet Abie; Mihret, Adane; Tamiru, Mekdes; Hailu, Elena; Olani, Abebe; Aliy, Abde; Sombo, Melaku; Lakew, Matios; Gumi, Balako; Ameni, Gobena; Wood, James L. N.; Berg, Stefan (Frontiers in Veterinary Science, 2020)
Bovine tuberculosis (bTB) is endemic in Ethiopia with higher prevalence in cattle, particularly in the central parts. Spread of Mycobacterium bovis (M. bovis) to wider regions is inevitable in uncontrolled conditions. This study was conducted to explore the pathology, characterize M. bovis strains and describe genotypic diversity to demonstrate possible epidemiological links in emerging dairy areas of Ethiopia, namely, Mekelle and Gondar. Twenty-seven bTB positive cattle identified by the Single Intradermal Comparative Cervical Tuberculin (SICCT) test were subjected to post-mortem inspection to determine lesion distribution and pathological score. Samples from tissues with visible tuberculous or suspected non-visible lesions were processed and cultured following a standard protocol. Isolates identified as M. bovis by Region of Difference (RD)-based Polymerase Chain Reaction (PCR) were also spoligotyped to determine their spoligotype patterns. Post-mortem inspection of visceral organs indicated bTB suggestive lesions in 41% of the animals, with 25% being in the lungs. Lymph nodes from 77% of the animals had lesions. Fifty-five strains identified from 24 of the slaughtered animals were confirmed as M. bovis. No other mycobacterial species were isolated. Spoligotyping classified strains from 21 of these animals into seven spoligotype patterns: SB0133, SB0134, SB1176, SB2233, SB2290, SB2467, and SB2520. More than one spoligotype were identified from five of these animals, and none of the last four spoligotypes had been reported in Ethiopia before. SB0134 was the most predominant type (47%) followed by SB0133 (25.5%). SB0133, SB2290, SB2467, and SB1176 are spoligotypes lacking spacers 3-7, characteristics of M. bovis strains of the African 2 (Af2) clonal complex, while SB0134, SB2233, and SB2520 do not belong to any of the established clonal complexes and likely to have a different evolutionary history. Despite a small sample size, the present study showed strain diversity with multiple genotypes identified in a single herd and even within a single animal, and the genotypes showed no sign of geographical localization, which could be a consequence of significant movement of bTB diseased cattle around the country, spreading the disease. Therefore, any future control programme of bTB in Ethiopia needs to address the risks of cattle movement.